PENGARUH MODEL WORD SQUARE TERHADAP HASIL BELAJAR MUATAN IPS SISWA KELAS IV SEKOLAH DASAR - Putri Amalia Ikhsani; Nurhasanah Nurhasanah; Heri Hadi Saputra (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine the effect of Word Square learning model on the social science learning outcomes of the fourth grade students at SDN Gugus II Kecamatan Lingsar in the academic year 2020/2021. The type of this study was experimental research with a nonequivalent control group design with a type of quasi experiment. The population in the study was students at grade IV SD Gugus II, Kecamatan Lingsar, totaling 108 students, while the samples were grade IV SD Gugus II Kecamatan Lingsar District, totaling 85 students. Data in this study were collected through documentation and questionnaires, while the instruments were social studies learning outcomes documents and Word Square model questionnaires. Then, the data were analyzed by the normality test, linearity test, and simple regression test in order to determine the effect of Word Square model on learning outcomes. The results of normality and linearity test obtained that the data were normally distributed and had a linear relationship. After going through the prerequisite test, a simple regression test was carried out obtaining the sig value. of 0.000 <0.05 or using a comparison of the value of tcount (3.974) > ttable (1.988). This means that Ha was accepted and H0 was rejected. Thus, Word Square learning model significantly influenced the social science learning outcomes of the fourth grade students of SDN Gugus II, Kecamatan Lingsar in the academic year 2020/2021.